PENGARUH PERLAKUAN METODE BIRTHING BALL TERHADAP PENURUNAN INTENSITAS NYERI KALA 1 FASE AKTIF - Wahyuningsih, Diyan (Jurnal LENTERA, 2024)
Childbirth is a natural thing and will definitely be experienced by every woman who has a partner. However, the fact that cannot be denied is that many women feel anxious before giving birth, which can be influenced by various factors. The aim of providing Endorphine Massage with lavender aromatherapy is to reduce the anxiety level of mothers in the first stage of labor at the Sekar Community Health Center, Bojonegoro Regency. The design provides instillation, massage, Endorphine Massage with lavender aromatherapy to reduce the anxiety level of mothers in the first stage of labor at the Sekar Community Health Center, Bojonegoro Regency. The results of the instillation, giving Endorphine Massage pills with lavender aromatherapy which has no side effects in reducing the anxiety level of mothers giving birth at the Sekar Community Health Center, Bojonegoro Regency, so that mothers can apply endorphine massage with lavender aromatherapy to reduce the level of anxiety in labor without causing side effects in reducing Anxiety level